Invulnerability of the Chief Executive and Democratic Sustainability in Nigeria: Issues and Challenges (Global Journal of Human-Social Science, 2017)
The debate on the invulnerability of the chief executive in modern democracy has raged on with no end in sight soon Executive recklessness and impunity seem to have been given a tacit constitutional approval as no criminal proceedings can be brought or continued against the President the Vice President the Governor and the Deputy Governor during their tenures in office though the provisions do not take cognisance of the statute of limitations as criminal charges could be commenced or continued after the tenures of the holders of these offices Equality before the law presupposes that the law should apply equally to the rulers and the ruled save for privileges permitted by the Constitution or other law In the words of that erudite jurist Lord Denning MR To every subject in this land no matter how powerful I would use Thomas Fuller s words over 300 years ago Be you never so high the law is above you 1 I Introduction Based on the above this paper examines the invulnerability of the heads of executive arm of government in the discharge of their constitutional duties It x-rays the origin of sovereign immunity of the chief executives in Nigerian polity and the effects of invulnerability of the chief executive on the political stability of the nation
Keywords: executive power; executive invulnerability; immunity; political stability